Real-world evidence of hyperbaric oxygen therapy on cardiovascular outcomes in patients with chronic osteomyelitis - Chi-Jung Tai; Chun-Kuan Lu; Chun-Ying Lee; Su-Shin Lee; Yi-Hsin Yang (Elsevier, 2023)
Background: The effectiveness of hyperbaric oxygen (HBO) therapy for chronic osteomyelitis remains inconclusive. In particular, recent studies have shown that chronic osteomyelitis is a crucial risk factor for cardiovascular diseases. However, the preventive effect of HBO on cardiovascular events has not been reported in patients with chronic osteomyelitis. Methods: We conducted a population-based cohort study to evaluate the impact of HBO on patients with chronic osteomyelitis. Overall, 5312 patients with chronic osteomyelitis were selected from the Taiwan National Health Insurance Database to evaluate the impact of HBO in patients with chronic osteomyelitis. Propensity-score (PS) matching and inverse probability weighting (IPTW) were employed to balance covariates between the HBO and non-HBO groups. The primary outcome was all-cause mortality. The secondary outcomes were myocardial infarction (MI) and stroke hospitalisation. Furthermore, we evaluated the appropriate timing for HBO intervention by the restricted cubic spline (RCS) functions. Results: After 1:4 PS-matching, the HBO group (n = 265) was associated with lower 1-year mortality (hazard ratio [HR], 0.49; 95 % confidence interval [CI], 0.25-0.95) than the non-HBO group (n = 994); this was consistent with the IPTW weighting results (HR, 0.25; 95 % CI, 0.20-0.33). The risk of stroke was lower in the HBO group (HR, 0.46; 95 % CI, 0.34-0.63) than that in the non-HBO group. However, HBO therapy failed to reduce the risk of MI. Using the RCS model, patients with intervals within 90 days (HR, 1.38; 95 % CI, 1.04-1.84) presented a significant risk of 1-year mortality. After 90 days, as the length of interval increased, the risk gradually decreased and became insignificant. Conclusion: The present study revealed that adjunctive HBO could benefit the 1-year mortality and stroke hospitalisation in patients with chronic osteomyelitis. HBO was recommended to be initiated within 90 days of chronic osteomyelitis hospitalisation.